If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + 1) + -9 = 6 Reorder the terms: 3(1 + t) + -9 = 6 (1 * 3 + t * 3) + -9 = 6 (3 + 3t) + -9 = 6 Reorder the terms: 3 + -9 + 3t = 6 Combine like terms: 3 + -9 = -6 -6 + 3t = 6 Solving -6 + 3t = 6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3t = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 3t = 6 + 6 3t = 6 + 6 Combine like terms: 6 + 6 = 12 3t = 12 Divide each side by '3'. t = 4 Simplifying t = 4
| 4(a+24)=16 | | 11-b=-5 | | 4(m-13)=16 | | 4a+24=72 | | (-42x)(2x)= | | x^4+x^2-1=0 | | 2x^4-14x^3+12x^2=0 | | (-4t)+(4t)-(-3t)= | | 7x-102+2x+93=90 | | 1-t+2=12 | | (10x)+(22x)= | | -6a=6ax-3ax-2ax-4x | | 4x+50=9x-10 | | 4x^3-16x^2+12x=0 | | 5-9(x+1)-3=5+3(9-3x)-81 | | (-6x)-(-6x)= | | 48-5x=4x+19 | | 12-8x=114-29x | | (-13t)+(14x)-(13t)= | | 145-4x=6x+15 | | 4-6x=13-9x | | -27-4(7x-8x)=x-18 | | 5x^2-27x-18=0 | | 4-p=6 | | 36x^2-24x=0 | | x^2+16x+64=36 | | 3x+3(5x-7x)=38-x | | 62-4x=7x+18 | | -20+2.5(2+2x)=10 | | 4x-10=20+2x | | 1.5(2+2x)-11=-17 | | 14x^2+7x-7=0 |